The former Yugoslavia at the turn of the twenty-first century : a guide to the economies in transition - Jeffries, Ian (Routledge studies of societies in transition ;, 2003)
The author presents a clear, detailed and accessible breakdown of the developments in; Bosnia-Hercegovina, Croatia, the Former Yugoslav Republic of Macedonia, Slovenia and the Federal Republic of Yugoslavia (Serbia and Montenegro).